Death of children by domestic accidents: unveiling the maternal experience - Maria Augusta Rocha Bezerra; Ruth Cardoso Rocha; Karla Nayalle de Souza Rocha; Diogo Filipe Santos Moura; Marialda Moreira Christoffel; Ivis Emília de Oliveira Souza; Silvana Santiago da Rocha (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to unveil the meanings of mothers whose children died as a result of domestic accidents in childhood. Methods: a qualitative research, in the light of Heideggerian phenomenology, with ten mothers whose children died from domestic accidents. It was carried out in a municipality of the Northeast Region of Brazil through phenomenological interviews between May and June 2017. The existential analytic was constituted by the comprehensive moments of the Heideggerian method. Results: the meanings unveiled pointed out that, to understand the sudden death of her child, the mother oscillates between feeling guilty, pointing and denying guilt. She reports emptiness, permanent pain, non-acceptance of her child's death, and the desire to keep him in her life. In this journey, the fear that brings limitations to her life and that of her other children is revealed. Final Considerations: it was revealed that the death of the child in infancy compromises the integrality of being a mother, indicating the need for systematic and continuous care for the adequate management of the emotional and social effects.